Beneficial effects of GABA-producing potential probiotic Limosilactobacillus fermentum L18 of human origin on intestinal permeability and human gut microbiota - Sumanpreet Kaur; Preeti Sharma; Melinda J. Mayer; Saskia Neuert; Arjan Narbad; Sukhraj Kaur (Microbial Cell Factories, 2023)
Abstract Background Gamma-aminobutyric acid (GABA) is a non-protein amino acid with neuroinhibitory, antidiabetic, and antihypertensive properties and is used as a drug for treating anxiety and depression. Some strains of lactobacilli are known to produce GABA and strengthen the gut barrier function which play an important role in ameliorating the effects caused by the pathogen on the gut barrier. The probiotic bacteria are also known to modulate the human fecal microbiota, however, the role of GABA-producing strains on the gut epithelium permeability and gut microbiota is not known. Results In this study, we report the production of high levels of GABA by potential probiotic bacterium Limosilactobacillus fermentum L18 for the first time. The kinetics of the production of GABA by L18 showed that the maximum production of GABA in the culture supernatant (CS) occurred at 24 h, whereas in fermented milk it took 48 h of fermentation. The effect of L18 on the restoration of lipopolysaccharide (LPS)-disrupted intestinal cell membrane permeability in Caco-2 monolayers showed that it significantly restored the transepithelial electrical resistance (TEER) values, by significantly increasing the levels of junction proteins, occludin and E-cadherin in L18 and LPS-treated Caco-2 cells as compared to only LPS-treated cells. The effect of GABA-secreting L18 on the metataxonome of human stool samples from healthy individuals was investigated by a batch fermentor that mimics the conditions of the human colon. Although, no differences were observed in the α and β diversities of the L18-treated and untreated samples at 24 h, the relative abundances of bacterial families Lactobacillaceae and Bifidobacteriaceae increased in the L18-treated group, but both decreased in the untreated groups. On the other hand, the relative abundance of Enterobacteriaceae decreased in the L18 samples but it increased in the untreated samples. Conclusion These results indicate that Li. fermentum L18 is a promising GABA-secreting strain that strengthens the gut epithelial barrier by increasing junction protein concentrations and positively modulating the gut microbiota. It has the potential to be used as a psychobiotic or for the production of functional foods for the management of anxiety-related illnesses.